Purchasing high-cost medical devices and equipment in hospitals: a systematic review - Farhad Shokraneh; Saba Hinrichs-Krapels; Bor Ditewig; Harriet Boulding; Anastasia Chalkidou; Jamie Erskine (BMJ Open, 2022)
Objectives To systematically review academic literature for studies on any processes, procedures, methods or approaches to purchasing high-cost medical devices and equipment within hospitals in high-income countries.Methods On 13 August 2020, we searched the following from inception: Cost-Effectiveness Analysis Registry, EconLit and ProQuest Dissertations & Theses A&I via ProQuest, Embase, MEDLINE, and MEDLINE in Process via Ovid SP, Google and Google Scholar, Health Management and Policy Database via Ovid SP, IEEE Xplore Digital Library, International HTA Database, NHS EED via CRD Web, Science Citation Index-Expanded, Conference Proceedings Citation Index-Science, and Emerging Sources Citation Index via Web of Science, Scopus, and Zetoc conference search. Studies were included if they described the approach to purchasing (also known as procurement or acquisition) of high-cost medical devices and/or equipment conducted within hospitals in high-income countries between 2000 and 2020. Studies were screened, data extracted and results summarised in tables under themes identified.Results Of 9437 records, 24 were included, based in 12 different countries and covering equipment types including surgical robots, medical imaging equipment, defibrillators and orthopaedic implants. We found heterogeneity in methods and approaches; including descriptions of processes taking place within or across hospitals (n=14), out of which three reported cost savings; empirical studies in which hospital records or participant data were analysed (n=8), and evaluations or pilots of proposed purchasing processes (n=2). Studies emphasise the importance of balancing technical, financial, safety and clinical requirements for device selection through multidisciplinary involvement (especially clinical engineers and clinicians) in decision-making, and the potential of increasing evidence-based purchasing decisions using approaches such as hospital-based health technology assessments, ergonomics and device ‘user trials’.Conclusions We highlight the need for more empirical work that evaluates purchasing approaches or interventions, and greater specificity in study reporting (eg, equipment type, evaluation outcomes) to build the evidence base required to influence policy and practice for medical equipment purchasing.Protocol registration This review was registered in Open Science Framework: Shokraneh F, Hinrichs-Krapels S, Chalkidou A et al. Purchasing high-cost medical equipment in hospitals in OECD countries: A systematic review. Open Science Framework 2021; doi:10.17605/OSF.IO/GTXN8. Available at: https://osf.io/gtxn8/ (accessed 12 February 2022).